2019
DOI: 10.1038/s42003-019-0357-y
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-mechanics of human collagen superstructures revealed by all-optical correlative micro-spectroscopies

Abstract: In every biological tissue, morphological and topological properties strongly affect its mechanical features and behaviour, so that ultrastructure, composition and mechanical parameters are intimately connected. Overall, it is their correct interplay that guarantees the tissue functionality. The development of experimental methods able to correlate these properties would open new opportunities both in the biological and the biomedical fields. Here, we report a correlative study intended to map supramolecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 59 publications
(68 reference statements)
0
35
0
Order By: Relevance
“…This technique gives global information on bone elasticity but does not allow one to investigate the microscale level because of the limited spatial resolution. Recently, a new method has been proposed to measure the mechanical properties of biological tissues, based on Brillouin micro-spectroscopy 2 7 The technique is based on the inelastic scattering of light from thermally activated acoustic waves propagating through the sample at GHz frequencies. Based on the light-scattering process, it has the great advantage of being non-destructive and contactless, since it does not need external probes but light.…”
Section: Introductionmentioning
confidence: 99%
“…This technique gives global information on bone elasticity but does not allow one to investigate the microscale level because of the limited spatial resolution. Recently, a new method has been proposed to measure the mechanical properties of biological tissues, based on Brillouin micro-spectroscopy 2 7 The technique is based on the inelastic scattering of light from thermally activated acoustic waves propagating through the sample at GHz frequencies. Based on the light-scattering process, it has the great advantage of being non-destructive and contactless, since it does not need external probes but light.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, collagen I and collagen II have been proven to efficiently produce SHG signals . SHG has been applied to investigate rat and human corneal samples . Collagen fibrils in cornea were observed under SHG microscopy without any labelling.…”
Section: Introductionmentioning
confidence: 99%
“…A recent work demonstrated that a more generalized model, considering both cylindrical and trigonal symmetry, could be used to describe the organization of collagen structure. 47 Such approach could provide improved results in human breast samples. 48 Following the experimental approach described herein, which was based on the calculation of the integrated anisotropy parameter values of different collagen types, the discrimination between benign and malignant cancer tissue samples could be achieved.…”
Section: Discussionmentioning
confidence: 99%